Population Pharmacokinetics of Brentuximab Vedotin in Adult and Pediatric Patients With Relapsed/Refractory Hematologic Malignancies: Model‐Informed Hypothesis Generation for Pediatric Dosing Regimens. (28th June 2020) - Suri, Ajit; Mould, Diane R.; Song, Gregory; Kinley, Judith; Venkatakrishnan, Karthik
Abstract: Prior pharmacokinetic (PK) analyses of the antibody‐drug conjugate (ADC) brentuximab vedotin (1.8 mg/kg every 3 weeks) in pediatric patients with relapsed/refractory hematologic malignancies found that patients aged <12 years exhibited decreased ADC area under the curve (AUC) compared with those aged ≥12 years. This population PK (POPPK) analysis used data from pediatric (NCT01492088) and adult (NCT00430846) studies of brentuximab vedotin to quantify body size effects on ADC exposure. Data were collected from 84 patients with a median age of 25.7 years (range, 7.7‐87.3 years), 34 of whom (40.5%) were aged <18 years; median patient weight was 67 kg (range, 21‐154 kg), and median body surface area was 1.8 m 2 (range, 0.87‐2.81 m 2 ). ADC PK was described by a linear 3‐compartment model with zero‐order input and first‐order elimination. POPPK modeling indicated that dosing brentuximab vedotin at 1.8 mg/kg every 3 weeks or 1.2 mg/kg every 2 weeks resulted in lower ADC AUC values in small/moderate‐sized pediatric patients (<28 kg and 28‐49 kg, respectively) compared with large pediatric/adult patients (50‐100 kg). Dosing at 71.5 mg/m 2 every 3 weeks and 47.7 mg/m 2 every 2 weeks was predicted to achieve comparable AUC values across all body weight ranges and a similar AUC to that in the 50‐ to 100‐kg group at the standard doses of 1.8 mg/kg every 3 weeks and 1.2 mg/kg every 2 weeks, respectively. These results have generated a hypothesis to support evaluation of brentuximab vedotin at 48 mg/m 2 every 2 weeks in combination with adriamycin, vinblastine, and dacarbazine chemotherapy in an ongoing pediatric trial in frontline Hodgkin lymphoma (NCT02979522).